THE EFFECT OF DIFFERENT INSULATION MATERIAL ON THERMAL COMFORT IN A BUILDING WITH NOZZLES COOLING SYSTEM - Kaygısız, Ali Çağlar; Kıstak, Celal; Eren, Haydar (My University, 2025)
A global analysis of energy consumption reveals a downward trend in capacity, while energy demand continues to increase in response to population growth. In this context, the significance of efficient energy utilization, particularly the reduction of heat losses in buildings, has grown considerably. Insulating buildings is a strategy that has the potential to minimize heat loss during winter months and overheating during summer months. This, in turn, can reduce the energy needed for heating and cooling systems, including air conditioners. The present study investigates the impact of insulation on thermal performance using a small, single-story wooden building model. The experimental design involved the insulation of the model's exterior walls with three distinct types of materials during the summer months. The experimenters recorded indoor and outdoor temperatures and calculated total heat loss (or gain) to assess the effects of insulation material on thermal comfort. The experiments were repeated with different building orientations, while radiation intensity and wind speed were also measured for a comprehensive analysis.
Keywords: Energy; Heat Transfer; Insulation; Termal Performance